A efetividade da proteção contra a despedida arbitrária, ou sem justa causa, nas relações de emprego, prevista na Constituição Federal - Cornélio, Raphael Lima Lemes (2019)
The theme proposed for this paper aims to analyze the extent to which the effectiveness of Constitutional protection against arbitrary or unfair dismissal, as set forth in article 7, I. Initially, the evolution of employment protection in Brazilian law will be exposed since its prediction. Eloy Chaves Law, its treatment in the Federal Constitution, the Consolidation of Labor Laws and various laws that dealt with the subject, going through the relativization of stability with the FGTS model, to finally reach the provisions of the 1988 Constitution. Then we will analyze the expressions arbitrary and unfair dismissal present in article 7, I, delimiting its concepts. In the following, the support forecasts for workers in exceptional difficulty will be analyzed. Issues relevant to collective dismissal will also be studied, especially due to the normative gaps in national law on the subject, a fact that leads us to address them also from the perspective of international labor law. The importance of international labor law is such that the issue of dismissal will be addressed within the regional blocs and ILO. Subsequently a topic that generates debate in the doctrine is about the effectiveness of fundamental rights in employment relations, and about the discussion between the ineffectiveness of Article 7, I, regarding the position that argues to be the same self-applicable, under penalty of transforming the Constitution in dead letter. This culminates with an analysis of the effects of our entire legal framework, its effect on waiver protection, and whether there is effectiveness in the protection provided for in the Federal Constitution